2013
DOI: 10.1088/0268-1242/28/3/035008
|View full text |Cite
|
Sign up to set email alerts
|

Perhydropolysilazane spin-on dielectrics for inter-layer-dielectric applications of sub-30 nm silicon technology

Abstract: Various material properties of the perhydropolysilazane spin-on dielectric (PHPS SOD) were examined and analyzed in this study as potential inter-layer dielectrics (ILDs) integrated for Si circuits of 30 nm technology or beyond. The spin-coated PHPS (18.5 wt%) layers converted at 650 • C showed comparable but less perfect thermal conversion to silica than the films converted at 1000 • C, however exhibiting excellent gap filling (15 nm gap opening, aspect ratio (AR) of ∼23) and planarization (degree of planariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Infrared spectra are shown in Figure while Table provides the IR peak assignments. , It has previously been shown that, above 300 °C, the hydrolysis of Si–N and Si–H bonds leads to the formation of a SiO 2 network. ,, In the case of CAPS, the main absorption bands are observed at approximately 1180 and 3360 cm –1 and correspond to the bend and stretch modes of N–H, respectively. In addition, bands at 920, 840, and 2160 cm –1 indicate the presence of Si–N and Si–H bonds in the CAPS film.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Infrared spectra are shown in Figure while Table provides the IR peak assignments. , It has previously been shown that, above 300 °C, the hydrolysis of Si–N and Si–H bonds leads to the formation of a SiO 2 network. ,, In the case of CAPS, the main absorption bands are observed at approximately 1180 and 3360 cm –1 and correspond to the bend and stretch modes of N–H, respectively. In addition, bands at 920, 840, and 2160 cm –1 indicate the presence of Si–N and Si–H bonds in the CAPS film.…”
Section: Results and Discussionmentioning
confidence: 99%
“…6 Polysilazane coatings can be transformed into SiCO, SiCN, or Si 3 N 4 ceramic coatings by pyrolyzing at high temperatures in air, N 2 , or Ar atmosphere. [7][8][9] They are promising candidates for inter-layer dielectrics, 10 oxidation, or wear protection coatings 11,12 for high-temperature applications because of their good thermal shock resistance and thermal stability. However, the high-temperature applications require processing temperatures beyond 800 C, which is impracticable for certain applications owing to the limitation of the substrate or manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment yielded a polysilazane with high molecular weight. Completely cured polysilazane remains optically clear and transparent yielding a very smooth surface [30][31][32][33]. For complete transformation of polysilazane to silica, different methods are being used that include: curing with heat, exposing to a catalyst, curing by irradiating with deep UV and a combination of the aforementioned methods [24,33].…”
Section: Introductionmentioning
confidence: 99%